International Skating Union: Special Regulations & Technical Rules Single & Pair Skating and Ice Dance 2012 as accepted by the 54th Ordinary Congress June 2012 (2012)
I. Special regulations single & Pair skating ice dance II. Technical rules single & Pair skating III. Technical rules ice dance